Preparation, Characterization and Theoretical Study of a New Chromate Ionic liquid: Triphenylphosphonium Tetrafluorochromate - Ghammamy, S.; Mehrani, K.; Giemechi, G.; Sedaghat, S. (Journal of Scientific Research, 2012)
The synthesis of triphenylphosphonium tetrafluorochromate (III) liquid (IL) is reported here. The product was characterized by spectroscopic and analytical methods such as, FT-IR, cyclic voltammetry, CHN, TGA and differential thermal analysis (DTA). Thermal decomposition of this compound showed multistage processes and also results show that this IL has excellent thermal stability below 100°C. In this paper, the optimized geometries and frequencies of the stationary point and the minimum-energy paths were calculated by using the DFT (B3LYP) methods with 6-311G* basis sets. From these calculations, optimized geometries, molecular parameters, and vibrational spectra of IL have been calculated. In addition, calculated frequencies were compared with the experimental frequencies after correction by the appropriate scaling factor. This comparison showed that our theoretical data are in good agreement with the experimental results. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.9915 J. Sci. Res. 4 (3), 649-656 (2012)